Development Of Extraction And Separation Techniques For The Determination Of Polycyclic Aromatic Hydrocarbons And Biogenic Amines In Food - Hor, Jia Yi (2024)
Polycyclic aromatic hydrocarbons (PAHs) and biogenic amines (BAs) are potential contaminants in various food products. Quantitative analysis of these contaminants in food is challenging due to their high physicochemical variability and complexity. This thesis describes the method developments for quantitative analysis of PAHs and BAs in selected food products.